Doctor’s Civil Responsibility in Medical Malpractice in Indonesia - Nurarafah, Nurarafah (Journal Research of Social Science, Economics, and Management, 2022)
In the perspective of civil law, medical malpractice is an unlawful act (onrechtmatige daad) in accordance with the provisions of the Civil Code (Burgerlijk Wetboek). This study aims to analyze the civil liability of a doctor in medical malpractice in Indonesia. This type of research is legalistic, doctrinal or normative. Based on the results of the study, a lawsuit against the law in medical malpractice is regulated in Article 1365 Burgerlijk Wetboek (BW) with elements such as the patient having to suffer losses, mistakes or negligence (other than private persons, hospitals). may also be liable for errors or omissions). negligence of employees), there is a causal relationship between loss and error, the act violates the law. In addition, the form of the doctor’s liability in acts against the law of medical malpractice based on Article 1365 BW can be in the form of material and immaterial compensation to patients.